2018
DOI: 10.1051/matecconf/201818302001
|View full text |Cite
|
Sign up to set email alerts
|

Tribological characteristics of Al/SiC/Gr hybrid composites

Abstract: Abstract. Metal matrix composites (MMCs) are considered as important engineering materials due to their excellent mechanical, as well as tribological properties. When the metal (or alloy) matrix is reinforced with two or more reinforcements, those composites are the so-called hybrid composites. The aluminum metal matrix composites, reinforced with silicon carbide (SiC) and graphite (Gr), are extensively used due to their high strength and wear resistance. The tribological characteristics of such materials are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…The powder metallurgy technique was used for the synthesis of HAMCs from the Al matrix and using SiC and Al 2 O 3 as primary reinforcements, and Gr and SCBA as secondary reinforcements. Using SiC and Al 2 O 3 as primary reinforcements within the range of 3-10 wt% yields superior physical, mechanical, and tribological properties [20,37].…”
Section: Synthesis Of Hamcs Using the Pm Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The powder metallurgy technique was used for the synthesis of HAMCs from the Al matrix and using SiC and Al 2 O 3 as primary reinforcements, and Gr and SCBA as secondary reinforcements. Using SiC and Al 2 O 3 as primary reinforcements within the range of 3-10 wt% yields superior physical, mechanical, and tribological properties [20,37].…”
Section: Synthesis Of Hamcs Using the Pm Processmentioning
confidence: 99%
“…Comparison of monolithic and single and hybrid reinforced aluminum matrix composites[14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…The influence of the load on the wear rate of the Al/SiC/Gr composite with a different mass percentage of SiC particles, in the presence of graphite, is shown in Fig.12 [44]. Based on the diagram in Fig.10, it can be concluded that the wear intensity increases with increasing load.…”
Section: Benefits and Improvements Provided By Application Of Aluminumentioning
confidence: 94%
“…The influence of the load on the coefficient of friction of the composite Al/SiC/Gr, with different mass percentage of SiC particles, is shown in Fig.11 [44]. In addition, the influence of the load on the coefficient of friction of the Al/SiC/Gr composite with different percentages of particle mass Gr particles and fixed 5% SiC in the total mass of the composite is shown, as shown in the Fig.12 [44].…”
Section: Benefits and Improvements Provided By Application Of Aluminumentioning
confidence: 97%
See 1 more Smart Citation